Cross-Cultural Adaptation of Health Literacy Instrument for Hispanic and Latino/a/e Communities - Jennifer Contreras; Chun Wang; Wendy Camelo Castillo; Juan Caicedo; Monica Guerrero Vázquez; Tania Robalino; Aida Hidalgo-Arroyo; Ester Villalonga-Olives (Health Literacy Research and Practice)
Hispanic and Latino/a/e individuals are more likely to have lower levels of health literacy compared to other ethnic and racial groups. Additionally, 32% of this population also has limited English proficiency. There is a need to develop culturally valid instruments in Spanish to assess health literacy in this population. The Health Literacy Skills Instrument Short Form (HLSI-SF) was developed and validated in English by RTI International, but not in Spanish. Our aim was to culturally adapt the HLSI-SF to be used for Hispanic and Latino/a/e individuals living in the United States. We followed the Patient-Reported Outcome Consortium guidelines for cross-cultural adaptation of measures for content and linguistic validity. This included two forward-translations, reconciliation, two back-translations, revision and harmonization, cognitive interviews (total of six), revision, external expert review, and final version. We involved an expert panel of health professionals and community representatives throughout the process. The panel (n = 4) all self-identified as Hispanic or Latino/a/e and were fluent in English and Spanish. To evaluate the adapted HLSI-SF measure, we conducted cognitive interviews through six online focus groups involving 22 Hispanic and Latino/a/e community members, followed by a psychometric assessment using a sample of 726 Hispanic and Latino/a/e individuals with Spanish as their primary language. Focus group-based cognitive interviews revealed that while most items on the adapted HLSI-SF measure performed well, some participants had difficulties with a few items, which may suggest limited health knowledge. Psychometric analyses revealed that all but the Nutrition Label and Calories items performed well. Further validation of the HLSI-SF is needed to produce a valid and reliable instrument to measure health literacy in Hispanic and Latino/a/e populations in the U.S. [HLRP: Health Literacy Research and Practice. 2025;9(3):e83–e92.]